Science for Architecture: Designing Architectural Research in Post-War Sweden - Frida Rosenberg (Footprint)
How did architectural research in Sweden become scientific in its approach rather than artistic, as architecture education in the post-war period was primarily influenced by the Bauhaus pedagogy? Via the American Bauhaus pedagogical developments taking place at the IIT and the GSD, Swedish architecture education adopted the artistic ‘learning by doing’ approach.